Effects of International Migration in Agriculture Sector of Nepal - Shrestha, Subhechchha (Journey for Sustainable Development and Peace Journal, 2026)
This paper aims to explore the multidimensional impact of international migration on agricultural sector of Nepal. It focuses on changes in labor force, land use, and remittance utilization. The systematic review of literature and regression analysis reveals that migration has resulted in significant labor shortages, land abandonment, and declining agricultural engagement particularly in hill regions. It has also enabled productivity gains through remittance financed investments in improved and modern technologies. There is emergence of feminization of agriculture due to outmigration of men members of the farming households. This is a major coping mechanism followed in the labor scarce situation. Regression analysis indicate that remittance inflows have negative effect on expanding paddy cultivation area but has a strong positive relationship with paddy productivity. This highlights the potential to improve yields through better inputs and technologies. The findings claim the necessity of policy interventions that could channel remittances toward productive agricultural uses and address the challenges of labor scarcity and gender inequality to ensure long-term agricultural sustainability in a migration driven economy of Nepal.